2013
DOI: 10.1016/j.bbadis.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of c-myc in hepatocytes promotes activation of hepatic stellate cells and facilitates the onset of liver fibrosis

Abstract: Overexpression of c-myc is a novel marker of liver fibrosis in man and mice. We conclude that chronic induction of c-myc especially in hepatocytes has the potential to prime resident HSC for activation, proliferation and myofibroblast differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…Recently, several studies suggested there existed crosstalk between hepatocytes and HSC, such as overexpression of c-Myc, p53 in hepatocytes contributed to HSC activation3637, yet hepatic HNF1a showed antifibrotic function. However, the role of hepatocytes in the activation of HSCs during chronic HBV infection progressed into liver cirrhosis has not been clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies suggested there existed crosstalk between hepatocytes and HSC, such as overexpression of c-Myc, p53 in hepatocytes contributed to HSC activation3637, yet hepatic HNF1a showed antifibrotic function. However, the role of hepatocytes in the activation of HSCs during chronic HBV infection progressed into liver cirrhosis has not been clearly elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is mediated in part by an inhibition of PPARγ and reduction of lipogenesis, plus increased PDGF-B expression in hepatocytes and subsequent paracrine crosstalk with HSCs. Interestingly, the increase in c-myc may result either from a direct inflammatory response to liver injury or from injury-induced gene amplification [139]. C-myc may be a target for HCC chemoprevention and fibrosis modulation.…”
Section: New and Emerging Pathways Of Hsc Activationmentioning
confidence: 98%
“…For example, c-myc is a central driver of cellular proliferation [137] and its amplification is commonly found in HCC [138]. It has recently been shown to be overexpressed in hepatocytes of human liver samples with advanced fibrosis and promotes a "profibrotic tissue environment" via pre-activation of HSCs, which primes them for a second profibrotic insult [139]. This effect is mediated in part by an inhibition of PPARγ and reduction of lipogenesis, plus increased PDGF-B expression in hepatocytes and subsequent paracrine crosstalk with HSCs.…”
Section: New and Emerging Pathways Of Hsc Activationmentioning
confidence: 99%
“…The Myc proteins are involved in major biological processes including proliferation, metabolism, cell cycle progression, apoptosis, cell growth and differentiation, fibrosis, and polarity (34)(35)(36) (Figure 1). All of these cellular functions are altered and ongoing in ADPKD.…”
Section: Myc Cellular Functionsmentioning
confidence: 99%